Systems engineering in the fourth industrial revolution : big data, novel technologies, and modern systems engineering - Kenett, Ron; Swarz, Robert S.; Zonnenshain, Avigdor (Wiley, 2020)
"This book addresses the changes in systems engineering (SE) prompted by the current industrial environment. Elements of importance in this environment are the shift towards data collection, availability and use in the design and development of systems and also in the later life-cycle stages of use and retirement. In addition, the book addresses the issues in a system in which the system involves data in its operation, contrasting with earlier approaches in which data and algorithm implementation were less involved in the function of the system. These issues are a significant contrast with typical applications of SE to date, in which systems have been conceived as relatively static and long time lines have been acceptable"--